Розробка рекомендаційної функції системи поширення квитків на публічні заходи - Згоденко, Д. Р.; Колесник, О. Б. (ХНУРЕ, 2025)
This paper discusses the integration of an information and recommendation system in an online ticket distribution platform for public events as an innovative approach to automate key business processes. By streamlining operations, reducing time and labor costs, and boosting ticket sales, this solution significantly enhances the overall efficiency of event organizers. Moreover, implementing a recommendation system increases customer loyalty and improves their purchasing experience by offering personalized event suggestions that align wІТh individual preferences, ultimately resulting in higher customer satisfaction and stronger revenue growth.
Keywords: публічний захід; квитки; система поширення; рекомендаційна функція